Tailoring Stark effect in the 1.54 µm emission of Er-doped ZnO thin films. (February 2021) - Ianhez-Pereira, Camila; Rodrigues, Ariano De Giovanni; de Godoy, Marcio Peron Franco
Abstract: We report a study on the infrared optical emission of Er 3+ inserted on ZnO hosts. The doping process was carried out during the growth of thin films by spray pyrolysis. The precursor solutions consisted of zinc acetate and erbium chloride proportionally diluted in distilled water, producing films in a clean and cost-effective process. The different molarity conditions employed here, M=10 −3 and M=10 −1, provided the growth of high textured c-axis, optical transparent ZnO, and white powder-like ZnO films, respectively. The infrared emissions at 0.8 eV (1.5 μm) are affected by the level manifolds due to the Stark effect, which is found to be strongly dependent on synthesis parameters. Lower crystallinity implies mitigation of the strong electric field in c-direction, reducing the intensity of the splitting caused by Stark effect. Graphical Abstract: Image, graphical abstract